Pyridine compound modified CuAu bimetallic nano hollow structure catalyst, preparation and application

By modifying the surface of CuAu catalyst with pyridine compounds to form a Cu+/Cu0@Au functionalized interface, the problem of weak electronic interaction in CuAu catalyst was solved, and efficient electroreduction of carbon dioxide to ethanol was achieved. The catalyst exhibits high activity and high selectivity at low potential.

CN121675015APending Publication Date: 2026-03-17HUAZHONG UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511910698.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-17
Publication Date
2026-03-17

AI Technical Summary

Technical Problem

Existing CuAu bimetallic catalysts suffer from insufficient electronic interaction between Au and Cu in the electrocatalytic reduction of carbon dioxide to ethanol, resulting in limited synergistic effects and low density of active sites on the catalyst surface, leading to low selectivity and efficiency in ethanol production.

Method used

By modifying the surface of CuAu bimetallic catalysts with pyridine compounds to form pyridine-modified Cu+/Cu0@Au functionalized interfaces, C-C coupling and intermediate adsorption are promoted, thus preparing pyridine-modified CuAu bimetallic hollow nanostructure catalysts.

Benefits of technology

It significantly improves the activity and selectivity of the catalyst, achieving a Faraday efficiency of 76%, and efficiently generates ethanol at low potential, solving the problems of low activity and poor selectivity of existing catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121675015A_ABST
    Figure CN121675015A_ABST
Patent Text Reader

Abstract

The invention relates to a pyridine compound modified CuAu bimetallic nano hollow structure catalyst, and preparation and application thereof, and belongs to the technical field of electro-catalysis. The preparation method comprises the following steps: dropwise adding a chloroauric acid solution into hollow Cu2O nano-particles to obtain a core-shell structure with gold nano-particles loaded on the surfaces of the hollow Cu2O nano-particles, then carrying out solvothermal reaction to obtain hollow CuAu nano-particles, and then adding a pyridine organic modifier to obtain the hollow CuAu nano-particles. The catalyst prepared by the invention has a Cu < + > / Cu0 at Au functionalized catalytic interface, realizes differential adsorption of * CO intermediates and subsequent hydrogenation reaction process, and promotes asymmetric * CO-* CHO coupling, so that the activity and selectivity of ethanol products are remarkably improved, and the Faraday efficiency can reach 76%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrocatalysis technology, and more specifically, to a CuAu bimetallic hollow nanostructure catalyst modified with pyridine compounds, its preparation and application, and particularly to the application of this catalyst in the electrocatalytic reduction of carbon dioxide to ethanol. Background Technology

[0002] With the acceleration of global industrialization, the large-scale use of fossil fuels has led to a continuous rise in atmospheric CO2 concentration, causing serious greenhouse effect and climate change problems. Electrocatalytic CO2 reduction reaction (CO2RR) technology can convert CO2 into high-value-added chemicals and fuels, while utilizing electricity generated from renewable energy sources (such as solar and wind power) to achieve carbon resource recycling, making it one of the important technological pathways to achieve carbon neutrality. Among the various products of electrocatalytic carbon dioxide reduction, ethanol stands out as one of the most valuable target products due to its high energy density (approximately 29.7 MJ / kg), ease of storage and transportation, and direct use as fuel or chemical feedstock. However, the electroreduction of CO2 to ethanol faces many challenges: for example, 1. The reaction pathway is complex. The formation of ethanol requires the transfer of 12 electrons and 12 protons, involving multiple elementary steps such as C-C coupling and CO bond breaking, making the reaction pathway complex and selective control difficult; 2. There are many competing reactions. There are multiple competing reactions in the CO2 reduction process, such as the hydrogen evolution reaction (HER), CO, and ethylene formation, resulting in a low Faraday efficiency for ethanol; 3. The catalyst performance is insufficient. Existing catalysts generally suffer from low activity, poor selectivity, and insufficient stability, making it difficult to meet the needs of industrial applications.

[0003] Copper-based catalysts, due to their unique d-electron structure, can moderately adsorb intermediates such as *CO, and are considered the most promising catalysts for the reduction of CO2 to multi-carbon products. However, single copper catalysts often exhibit low selectivity and produce numerous byproducts. Recent studies have found that by constructing Cu... + / Cu 0 Interfacial metal catalysts and molecular functionalization modifications can regulate electronic structure, optimize intermediate adsorption, and promote C-C coupling, thereby improving the selectivity of target products. Au, as an excellent CO generation catalyst, can efficiently reduce CO2 to the *CO intermediate. Constructing a CuAu bimetallic catalyst by combining Au and Cu holds promise for utilizing the synergistic effect of the *CO intermediate generated by Au and the active sites on the Cu surface to promote C-C coupling and the formation of multi-carbon products. However, existing AuCu metal catalysts still suffer from insufficiently strong electronic interactions between Au and Cu, limited synergistic effects, and low density of active sites on the catalyst surface. Therefore, developing high-performance CuAu bimetallic catalysts to improve the efficiency and selectivity of CO2 electroreduction to ethanol has significant scientific and practical value. Summary of the Invention

[0004] This invention provides a pyridine-modified CuAu bimetallic hollow nanostructure catalyst, its preparation, and its application. The preparation method involves adding chloroauric acid solution dropwise to hollow Cu₂O nanoparticles to obtain a core-shell structure of gold nanoparticles loaded on the surface of the hollow Cu₂O nanoparticles. Then, a solvothermal reaction is performed to obtain hollow CuAu nanoparticles. Finally, a pyridine-based organic modifier is added to obtain the pyridine-modified CuAu bimetallic hollow nanostructure catalyst. The pyridine-modified CuAu bimetallic hollow nanostructure catalyst prepared by this invention exhibits the characteristic of pyridine-modified Cu… + / Cu 0 The functionalized interface of @Au exhibits excellent catalytic performance in the electrocatalytic reduction of ethanol from carbon dioxide, demonstrating high activity and selectivity at low potentials. This solves the technical problems of low activity and poor selectivity in existing electrocatalytic carbon dioxide catalysts.

[0005] According to a first aspect of the present invention, a method for preparing a CuAu bimetallic hollow nanostructure catalyst modified with a pyridine compound is provided, comprising the following steps: (1) Hollow Cu2O nanoparticles were dispersed in a surfactant and then chloroauric acid solution was added dropwise to obtain a core-shell structure of gold nanoparticles loaded on the surface of hollow Cu2O nanoparticles. (2) The core-shell structure of gold nanoparticles loaded on the surface of hollow Cu2O nanoparticles obtained in step (1) is dispersed with surfactant in an alcohol organic compound, and then a solvothermal reaction is carried out to obtain hollow CuAu nanoparticles. (3) Disperse the hollow CuAu nanoparticles obtained in step (2) in an organic solvent, and then add a pyridine organic modifier to obtain a CuAu bimetallic hollow nanostructure catalyst modified with a pyridine compound.

[0006] Preferably, in step (3), the pyridine organic modifier is one or more of pyridine, 2-dimethylaminopyridine, 3-dimethylaminopyridine and 4-aminopyridine.

[0007] Preferably, in step (2), the temperature of the solvothermal reaction is 100-200℃.

[0008] Preferably, in step (1), the hollow Cu2O nanoparticles are prepared by the following method: copper salt and surfactant are dissolved in water, mixed thoroughly, and then a reducing agent is added to obtain hollow Cu2O nanoparticles.

[0009] Preferably, the copper salt is one or more of copper sulfate, copper nitrate, copper chloride, and copper acetate.

[0010] Preferably, the alcoholic organic compound is at least one selected from ethylene glycol, diethylene glycol, triethylene glycol trioxide, and tetraethylene glycol trioxide.

[0011] According to another aspect of the present invention, a CuAu bimetallic hollow nanostructure catalyst modified with pyridine compounds prepared by any one of the methods described herein is provided.

[0012] Preferably, the particle size of the CuAu bimetallic hollow nanostructure catalyst modified with pyridine compounds is 200 nm to 1 μm.

[0013] According to another aspect of the present invention, the application of the pyridine-modified CuAu bimetallic hollow nanostructure catalyst is provided in the electrocatalytic reduction of carbon dioxide to ethanol.

[0014] Preferably, the application specifically involves: drop-coating the pyridine-modified CuAu bimetallic hollow nanostructure catalyst onto a glassy carbon electrode as the working electrode, using silver-silver chloride as the reference electrode, a platinum mesh as the counter electrode, and using a carbon dioxide-saturated potassium bicarbonate solution as the electrolyte to carry out an electrocatalytic carbon dioxide reduction reaction in an H-type electrolytic cell.

[0015] In summary, compared with the prior art, the above-described technical solutions conceived by this invention mainly possess the following technical advantages: (1) The preparation method provided by the present invention can prepare stable pyridine compounds modified Cu + / Cu 0 The functionalized interface of Au@Cu2O enables the catalyst to adsorb *CO intermediates and subsequent hydrogenation reactions, promoting asymmetric *CO-*CHO coupling and lowering the energy barrier of CC coupling reactions. This significantly improves the activity and selectivity for ethanol products, exhibiting excellent catalytic performance for the electrochemical reduction of carbon dioxide to ethanol. On the one hand, during the solvothermal reaction, Cu in Au@Cu2O... + Partially reduced to Cu 0 Cu + / Cu 0 A functional interface for coexistence. Based on XPS test results from the embodiments, Cu on the surface of the 4-AP@CuAu nanomaterial... + Cu 0 Cu 2+ The simultaneous presence of these elements indicates that the reaction conditions were precisely controlled. Meanwhile, the solvothermal reaction promoted partial alloying of Au and Cu (XRD diffraction patterns showed a shift in diffraction peaks relative to pure Cu and Au), confirming the formation of the CuAu alloy and enhancing the electronic interactions and synergistic effects between Au and Cu. On the other hand, 4-AP modification on Cu... + / Cu0 At the catalytic interface of @Au, through the interaction between its nitrogen-containing pyridine ring structure and the metal surface, it can not only differentially adsorb and stabilize *CO intermediates, but also effectively promote CC coupling reactions, enabling the electrocatalytic reduction of CO2 to proceed efficiently toward ethanol products.

[0016] (2) The catalyst prepared by this invention has Cu modified with pyridine compounds. + / Cu 0 The functionalized interface of @Au exhibits excellent catalytic performance in the electrocatalytic reduction of ethanol from carbon dioxide, with high activity and high selectivity at low potential (-0.4Vvs RHE).

[0017] (3) The CuAu bimetallic hollow nanostructure catalyst modified with pyridine compounds prepared in this invention has high selectivity for the electrochemical reduction of carbon dioxide to ethanol, with a Faraday efficiency of up to 76%, which is significantly better than most existing catalysts.

[0018] (4) The catalyst of the present invention has a unique nano-hollow structure, which provides more active sites and optimized mass transfer channels, which is beneficial to improving catalytic efficiency and stability.

[0019] (5) The method for preparing CuAu bimetallic hollow nanostructure catalyst modified with pyridine compounds provided by the present invention is simple, the reaction conditions are controllable, and the reproducibility is high. Attached Figure Description

[0020] Figure 1 TEM image of the 4-AP@CuAu catalyst.

[0021] Figure 2 The XRD pattern of the 4-AP@CuAu catalyst is shown.

[0022] Figure 3 Cu Auger photoelectron spectra of the 4-AP@CuAu catalyst.

[0023] Figure 4 TEM image of the 4-AP@CuAu-1 catalyst.

[0024] Figure 5 TEM image of the 4-AP@CuAu-6 catalyst.

[0025] Figure 6 This is a TEM image of the Au@Cu2O catalyst.

[0026] Figure 7 The FE distribution of the 4-AP@CuAu catalyst under different applied voltages is shown in the figure.

[0027] Figure 8This is a graph showing the FE distribution of the CuAu catalyst under different applied voltages.

[0028] Figure 9 The FE distribution of the 4-AP@CuAu-1 catalyst under different applied voltages is shown in the figure.

[0029] Figure 10 The figure shows the FE distribution of the Au@Cu2O catalyst under different applied voltages. Detailed Implementation

[0030] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. Furthermore, the technical features involved in the various embodiments of this invention described below can be combined with each other as long as they do not conflict with each other.

[0031] This invention discloses a pyridine-modified CuAu bimetallic hollow nanostructure catalyst, the preparation method of which includes the following steps: (1) Dissolve copper salt and polyvinylpyrrolidone in deionized water, sonicate to disperse them evenly, add reducing agent hydrazine hydrate solution, stir the reaction at a constant speed to obtain hollow Cu2O nanoparticles. (2) Hollow Cu2O nanoparticles were dispersed in polyvinylpyrrolidone solution, and ultrasonically dispersed to make them uniform. Then, chloroauric acid solution was added dropwise and stirred at a constant speed to produce an electro-displacement redox reaction, in which gold was replaced by copper to obtain hollow Au@Cu2O nanoparticles. (3) Hollow Au@Cu2O nanoparticles and polyvinylpyrrolidone were dispersed in an alcohol organic compound solvent and reacted at high temperature. The product was then post-treated to obtain hollow CuAu nanoparticles. (4) Disperse hollow CuAu nanoparticles in isopropanol, then add an organic modifier and disperse evenly to obtain a CuAu bimetallic hollow nanostructure catalyst modified with pyridine compounds.

[0032] In some embodiments, the copper salt in step (1) is one or more of copper sulfate pentahydrate, copper nitrate trihydrate, copper chloride dihydrate, and copper acetate monohydrate.

[0033] In some embodiments, the copper salt in step (1) is copper nitrate trihydrate.

[0034] In some embodiments, the concentration of the copper salt in step (1) is 0.1 to 1 M, and the mass fraction of the hydrazine hydrate solution is 10 to 60%.

[0035] In some embodiments, the concentration of the chloroauric acid solution in step (2) is 1–25 mM.

[0036] In some embodiments, the stirring speed described in steps (1) and (2) is 50-500 rpm.

[0037] In some embodiments, the alcohol organic compound solvent in step (3) is one or more of ethylene glycol, diethylene glycol, triethylene glycol trioxide, and tetraethylene glycol trioxide; In some embodiments, the organic compound in step (4) is one or more of pyridine, 2-dimethylaminopyridine, 3-dimethylaminopyridine, and 4-aminopyridine.

[0038] In some embodiments, the reaction temperature in step (3) is 100-200°C.

[0039] In some embodiments, steps (1), (2) and (4) are performed at room temperature.

[0040] In some embodiments, the high-temperature reaction in step (3) involves transferring the mixture to a stainless steel autoclave lined with polytetrafluoroethylene, sealing it, and reacting for 1-10 hours.

[0041] This invention also provides the application of the prepared pyridine-modified CuAu bimetallic hollow nanostructure catalyst in the electrocatalytic reduction of carbon dioxide to ethanol.

[0042] In some embodiments, the application specifically involves: a CuAu bimetallic hollow nanostructure catalyst modified with pyridine compounds being drop-coated onto a glassy carbon electrode as the working electrode, silver-silver chloride as the reference electrode, a platinum sheet as the counter electrode, and a carbon dioxide-saturated potassium bicarbonate solution as the electrolyte, and then carrying out an electrocatalytic carbon dioxide reduction reaction in an H-type electrolytic cell.

[0043] Preferably, the concentration of the potassium bicarbonate solution is 0.1-0.5 mol / L.

[0044] The following are specific embodiments. Example 1: Preparation of 4-AP@CuAu hollow nanostructure catalyst (1) Weigh 2.416g of copper nitrate trihydrate and 2g of polyvinylpyrrolidone, dissolve them in 200 mL of deionized water, and place them in an ultrasonic machine for 10 minutes to ensure that the solids are completely dissolved. (2) Stir the mixed solution in step (1) at a constant speed, add hydrazine hydrate solution as a reducing agent, and after reacting for 2 minutes, obtain Cu2O nanoparticles, and wash them three times by centrifugation with ethanol. (3) Weigh 0.5g of polyvinylpyrrolidone, dissolve it in 100 mL of deionized water, sonicate for 10 minutes to ensure that the solid is completely dissolved, then add hollow Cu2O nanoparticles and sonicate them to disperse evenly in the polyvinylpyrrolidone solution. (4) Stir the hollow Cu2O nanoparticle suspension that was uniformly dispersed in step (3) at a constant speed, add 2 mL of chloroauric acid solution with a concentration of 50 mM to it, and after reacting for 20 minutes, hollow Au@Cu2O nanoparticles are obtained and washed three times by centrifugation with ethanol. (5) Weigh 0.25g of polyvinylpyrrolidone, dissolve it in 3mL of ethanol, sonicate for 10 minutes to ensure that the solid is completely dissolved, then add Au@Cu2O nanoparticles and disperse them in the polyvinylpyrrolidone solution, sonicate for 6 minutes to make them evenly dispersed, and finally add 60mL of diethylene glycol solvent, sonicate again for 6 minutes to make them fully dispersed. (6) Transfer the uniformly dispersed hollow Au@Cu2O nanoparticle suspension from step (5) into a stainless steel autoclave lined with polytetrafluoroethylene, react in an oven at 170°C for 3 hours, cool naturally to room temperature after reaction, and wash three times with ethanol by centrifugation to obtain hollow CuAu nanoparticles. (7) Weigh 100 mg of 4-AP (4-aminopyridine), dissolve it in 10 mL of isopropanol, sonicate for 10 minutes to ensure that the solid is completely dissolved, and then add the CuAu nanoparticles obtained in step (6) and disperse them evenly to obtain 4-AP@CuAu nano hollow structure catalyst.

[0045] TEM tests were performed on the 4-AP@CuAu prepared in Example 1, and the results are as follows: Figure 1 As shown, 4-AP@CuAu has a diameter of approximately 280 nm and exhibits a hollow internal structure.

[0046] XRD tests were performed on the 4-AP@CuAu prepared in Example 1, and the results are as follows: Figure 2 As shown, the diffraction peaks in the XRD diffraction pattern are shifted relative to pure Cu and Au, indicating the formation of a CuAu alloy. Furthermore, the characteristic diffraction peaks match the standard cards for Cu2O and Cu, confirming the synthesis of the CuAu material.

[0047] XPS testing was performed on the 4-AP@CuAu prepared in Example 1, and the results are as follows: Figure 3 As shown, the Cu Auger photoelectron spectrum indicates that Cu on the surface of the 4-AP@CuAu nanomaterial + Cu 0 Cu 2+ Simultaneously, some Cu + Reduced to Cu 0 .

[0048] Example 2 Using the method of Example 1, the reaction time in step (6) was changed to 1 hour to obtain catalyst 4-AP@CuAu-1.

[0049] TEM tests were performed on the 4-AP@CuAu-1 prepared in Example 2, and the results are as follows: Figure 4 As shown, 4-AP@CuAu-1 has a diameter of approximately 240 nm and exhibits a hollow structure, with a degree of hollowness slightly less than that of 4-AP@CuAu in Example 1.

[0050] Example 3 Using the method of Example 1, the reaction time in step (6) was changed to 6 hours to obtain catalyst 4-AP@CuAu-6.

[0051] The 4-AP@CuAu-6 prepared in Example 3 was subjected to TEM testing, and the results are as follows: Figure 5 As shown, the 4-AP@CuAu-6 hollow structure fractured.

[0052] Comparative example Au@Cu2O Using the method of Example 1, Au@Cu2O nanoparticles were synthesized up to step (4) to obtain hollow Au@Cu2O nanoparticles.

[0053] TEM tests were performed on the Au@Cu2O prepared in the comparative example, and the results are as follows: Figure 6 As shown, Au@Cu2O has a diameter of approximately 230 nm, exhibits a hollow structure, and contains fine Au nanoparticles on the surface of the Cu2O shell.

[0054] Example 4: Application of the catalyst for the electroreduction of carbon dioxide The 4-AP@CuAu catalyst from Example 1 was used for electrocatalytic carbon dioxide reduction, and the steps are as follows: (1) Preparation of working electrode 20 μL of Nafion was dispersed in 1 mL of 4-AP@CuAu catalyst ink, sonicated for 10 minutes, and then 400 μL of the suspension was evenly dropped onto a 2.0 cm² plate using a pipette. 2 The 4-AP@CuAu working electrode is obtained by drying the surface of the carbon paper electrode with an infrared lamp.

[0055] (2) Electrocatalytic carbon dioxide reduction reaction The electrocatalytic reduction of carbon dioxide was carried out in an H-type electrolytic cell with a three-electrode system, where the cathode and anode were separated by a proton exchange membrane. A 4-AP@CuAu nanocatalyst was drop-coated onto a glassy carbon electrode to form the working electrode. A silver-silver chloride electrode was used as the reference electrode, and a platinum mesh electrode was used as the counter electrode. The electrolyte was a CO2-saturated 0.1 mol / L potassium bicarbonate aqueous solution. The electrochemical reduction of carbon dioxide was carried out under constant voltage, with carbon dioxide continuously introduced during the reaction. The product distribution of the 4-AP@CuAu nanocatalyst for the electrocatalytic reduction of carbon dioxide at different voltages (-0.4 V vs. RHE, -0.6 V vs. RHE, -0.8 V vs. RHE, -1.0 V vs. RHE, and -1.2 V vs. RHE) is shown below. Figure 7 As shown, H2 is a byproduct, and the main products of carbon dioxide reduction are CO and EtOH. The 4-AP@CuAu nanocatalyst exhibits the lowest selectivity for H2 at -0.4 V vs .RHE, indicating that the hydrogen evolution side reaction can be effectively suppressed at this potential, and the electrocatalytic activity for carbon dioxide reduction is the highest. At this potential, the 4-AP@CuAu nanocatalyst demonstrates the highest selectivity for ethanol products, with a Faraday efficiency of 76%. Figure 8 , Figure 9 The image shows the Faradaic efficiency of the CuAu and 4-AP@CuAu-1 nanocatalysts prepared in Examples 1 and 2 for the electrochemical reduction of the main products of CO2 reduction. The ethanol Faradaic efficiencies of the unmodified CuAu nanocatalyst and the 4-AP@CuAu-1 nanocatalyst are only 8% and 19%, respectively. Figure 10 As shown, the Au@Cu2O nanocatalyst prepared in the comparative example exhibits a Faradaic efficiency of 11% and an H2 Faradaic efficiency of 75% in the electrocatalytic reduction of carbon dioxide to ethanol at -0.4 V vs. RHE. These results fully demonstrate that the AP@CuAu catalyst with its unique hollow structure possesses significantly higher electrochemical reduction performance for CO2 to ethanol.

[0056] Those skilled in the art will readily understand that the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A preparation method of a CuAu bimetallic nanohollow structure catalyst modified by a pyridine compound, characterized in that, The method comprises the following steps: (1) dispersing hollow Cu2O nanoparticles in a surfactant, then adding a chloroauric acid solution dropwise to obtain a core-shell structure of hollow Cu2O nanoparticles loaded with gold nanoparticles on the surface; (2) dispersing the core-shell structure of hollow Cu2O nanoparticles loaded with gold nanoparticles obtained in step (1) in an alcohol organic compound together with a surfactant, then performing a solvothermal reaction to obtain hollow CuAu nanoparticles; (3) dispersing the hollow CuAu nanoparticles obtained in step (2) in an organic solvent, then adding a pyridine organic modifier to obtain a pyridine compound modified CuAu bimetallic nano hollow structure catalyst.

2. The method for preparing a pyridine-modified CuAu bimetallic nanocave structure catalyst according to claim 1, wherein, In step (3), the pyridine organic modifier is one or more of pyridine, 2-dimethylamino pyridine, 3-dimethylamino pyridine and 4-aminopyridine.

3. The method for preparing the CuAu bimetallic hollow nanostructure catalyst modified with pyridine compounds as described in claim 1, characterized in that, In step (2), the temperature of the solvothermal reaction is 100-200 DEG C.

4. The method for preparing a pyridine-modified CuAu bimetallic nanocavity structure catalyst according to claim 1, wherein, In step (1), the hollow Cu2O nanoparticles are prepared by the following method: dissolving a copper salt and a surfactant in water, thoroughly mixing, then adding a reducing agent to obtain hollow Cu2O nanoparticles.

5. The method for preparing the CuAu bimetallic hollow nanostructure catalyst modified with pyridine compounds as described in claim 4, characterized in that, The copper salt is one or more of copper sulfate, copper nitrate, copper chloride and copper acetate.

6. The method for preparing a pyridine-modified CuAu bimetallic nanocave structure catalyst according to claim 1, wherein, The alcohol organic compound is at least one of ethylene glycol, diethylene glycol, triethylene glycol and tetraethylene glycol.

7. The pyridine compound modified CuAu bimetallic nano hollow structure catalyst prepared by the method of any one of claims 1-6.

8. The pyridine-modified CuAu bimetallic nanocave structure catalyst of claim 7, wherein, The particle size of the pyridine compound modified CuAu bimetallic nano hollow structure catalyst is 200 nm-1 μm.

9. Use of the pyridine compound modified CuAu bimetallic nano hollow structure catalyst of claim 7 or 8 in electrocatalytic reduction of carbon dioxide to generate ethanol.

10. Use according to claim 9, wherein The use specifically comprises: dropping the pyridine compound modified CuAu bimetallic nano hollow structure catalyst on a glassy carbon electrode as a working electrode, using silver-silver chloride as a reference electrode, using a platinum mesh as a counter electrode, using carbon dioxide saturated potassium bicarbonate solution as an electrolyte, and performing an electrocatalytic carbon dioxide reduction reaction in an H-type electrolytic cell.